2013
DOI: 10.1089/apc.2013.0128
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Smoking in HIV-Infected Patients and Potential Barriers to Cessation

Abstract: Smoking is common in patients with HIV and is associated with increased morbidity and mortality. With the goal of targeting future cessation interventions, we sought to identify factors associated with smoking status, readiness and confidence in cessation, and success in quitting. As part of a larger study in New York City assessing predictors of chronic obstructive pulmonary disease (COPD), we enrolled HIV-infected subjects at least 35 years of age without known asthma or COPD. Current smokers received detail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 29 publications
(42 reference statements)
1
31
2
Order By: Relevance
“…Moreover, these findings highlight the duty of physicians treating patients with HIV to address contributing risks for lung disease such as cigarette smoking. 50 …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, these findings highlight the duty of physicians treating patients with HIV to address contributing risks for lung disease such as cigarette smoking. 50 …”
Section: Discussionmentioning
confidence: 99%
“…30 Evaluation included quantification of smoking exposure, marijuana and other illicit drug exposure, and a review of both HIV and opportunistic infection history. At the time of this study, ''undetectable'' viral load was defined at < 20 copies/mL, but the cutoff for undetectable varied when considering historical values in the chart.…”
Section: Testing Proceduresmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] Patients with HIV/AIDS also have increased barriers to smoking cessation, which adds to the risk for COPD over time. 30 Prior pulmonary infection with Pneumocystis jiroveci or other pathogens may also influence lung function. 19,24 Studies show that in addition, HIV infected patients with higher HIV viral loads or lower CD4 T-cell counts have more rapid decline in pulmonary function, worse disease, and likely worse diffusing capacity than similar patients without HIV.…”
mentioning
confidence: 99%
“…Current and former smokers were nearly twice as likely to have ever used marijuana, cocaine, amphetamine, or opiates and were three times as likely to have entered substance abuse treatment relative to never smokers. Recent studies with HIV populations have noted a similar association between smoking and substance use among PLHIV (Shirley et al, 2013) and suggest that HIV-infected smokers may represent a group of individuals with multiple addictions who are resistant to or unable to quit smoking and other drug use.…”
Section: Discussionmentioning
confidence: 88%
“…Since smoking is one of the biggest modifiable risk factors for cardiovascular and pulmonary diseases specifically in PLHIV, cessation strategies targeting this population are particularly relevant (Fiore et al, 2008; The Antiretroviral Therapy Cohort Collaboration, 2008). PLHIV smokers face unique barriers to smoking cessation, such as high rates of comorbid drug and alcohol use and mental illness (Bing et al, 2001), unemployment and lower socioeconomic status, lower quality of life (Shirley et al, 2013), inadequate social support (Gostin & Weber, 1998), and reliance on cigarettes as a coping mechanism for the stress associated with their illness (Helleberg et al, 2013). The Guidelines for Treating Tobacco Use and Dependence (Fiore et al, 2008) noted that studies examining smoking cessation interventions among HIV-infected patients are limited and generally show low rates of smoking cessation (Cummins et al, 2005; Fingeret et al, 2007; Ingersoll et al, 2009; Lloyd-Richardson et al, 2009; Vidrine et al, 2006), although more recent studies have shown cessation rates in this population ranging from 15% to 29% at 3 month follow-ups (Humfleet et al, 2013; Gritz et al, 2013).…”
Section: Introductionmentioning
confidence: 99%